Factors affecting early mobilization among critically Ill patients in Southern West Bank Hospitals. - Beesan Nassar; Moath Abu Ejheisheh; Ibrahim Aqtam; Ahmad Ayed; Ahmad Batran (PLoS ONE, 2025)
Introduction Early mobilization (EM) among critically ill patients is important to reduce complications such as ICU-acquired weakness and improve recovery outcomes. This study assessed factors influencing EM in Southern West Bank hospitals. Methods A cross-sectional study was conducted using the PERME ICU Mobility Score. Data were analyzed using SPSS to evaluate associations between mobility outcomes, demographics, BMI, and reasons for hospitalization. Inclusion criteria focused on critically ill patients admitted to ICUs for 2-5 days. Results Among 150 participants, the highest PERME ICU Mobility Score was observed in abdominal pain patients (mean = 28.0, SD = 0.0), reflecting minimal barriers, while respiratory patients scored lowest (mean = 6.9, SD = 6.9). No significant differences were found by age, gender, or BMI (p > 0.05). Seventy patients (46.7%) were awake/alert upon admission, while 39 (26%) were unresponsive. Pain or inability to determine pain levels was reported by 99 patients (66%). Conclusion Respiratory conditions and pain were critical barriers to EM. Demographic factors did not influence outcomes, but targeted pain management and condition-specific protocols are needed. The SD of 0.0 for abdominal pain patients suggests homogeneity in this subgroup, warranting further investigation.